Clinical efficacy of different therapeutic options for knee osteoarthritis: A network meta-analysis based on randomized clinical trials - Xiao Chen; Yuanhe Fan; Hongliang Tu; Yuan Luo (PLoS ONE, 2025)
Objective To assess and compare the clinical efficacy of various therapeutic options in treating patients with knee osteoarthritis (KOA). Methods We performed a comprehensive search of PubMed, Embase, OVID, Cochrane Library and Web of Science databases from their inception to December 10th, 2023, identifying randomized controlled trials (RCTs) examining the effects of therapeutic options on KOA. Two researchers independently performed literature screening, data extraction, data collection and organization, and quality assessment. The data obtained were subjected to statistical analysis and graphical representation using Stata 17.0 software. Results A total of 139 RCTs encompassing 9644 KOA patients and involving 12 therapeutic options were included. These interventions were low level laser therapy (LLLT), high intensity laser therapy (HILT), transcutaneous electrical nerve stimulation (TENS), interferential current (IFC), short wave diathermy, ultrasound, lateral wedged insole, knee brace, exercise, hydrotherapy, kinesio taping (KT) and extracorporeal shock wave therapy (ESWT). Regarding the WOMAC pain score, knee brace was determined to be the most likely to yield the best results, followed by exercise and HILT, ultrasound was worst intervention. In terms of WOMAC function score, knee brace emerged as the technique with the highest likelihood of being optimal, followed in sequence by hydrotherapy and ESWT, ultrasound was worst intervention. Knee brace ranked highest in effectiveness concerning the WOMAC stiffness score, followed by exercise and hydrotherapy. For the total WOMAC score, hydrotherapy demonstrated the highest probability of being the best technique, followed by exercise and HILT, short wave diathermy was worst intervention. In addressing VAS-rest, hydrotherapy exhibited the greatest likelihood of being the optimum technique, followed by HILT and LLLT. In terms of VAS-activity, knee brace had the highest probability of being the best technique, followed by LLLT and exercise, ultrasound was worst intervention. Overall, based on the results obtained from the SUCRA for all outcomes, knee brace had the highest probability of being the best technique, followed by hydrotherapy and exercise. Conclusion The findings suggest that knee brace may be the most recommended therapeutic option for the knee osteoarthritis, followed by hydrotherapy and exercise.